E-business adoption among homestay businesses: the Sarawak experience / Muhammad Omar …[et al.] - Omar, Muhammad; Kasuma, Jati; Asit, Roystance; Achan, Pauline; Mojolou, Dean Nelson (Universiti Teknologi Mara Selangor, 2015)
Information technology (IT) is now universally deemed by business organizations as an essential tool that they use to run their business activities and processes. The escalation of internet penetration in Sarawak has augmented new opportunities to the small medium enterprises (SMEs) to adopt e-business toward sustaining their businesses. The objectives of this study are to identify factors that influence e-business adoption among homestays in Kuching, Sarawak and to determine which factor has the most significant influence in its adoption. For the purpose of this study, the reviewed IT adoption model used is the technology-organizationenvironment (TOE) framework. This framework identifies three elements that drive the adoption of technology which are technological, organizational and environmental factors. A total of 150 homestay businesses within the city of Kuching were chosen to participate in the survey. Data were analysed using correlation analysis and multiple regression analysis. The findings indicated that organizational factor has the most significant influence on e-business adoption among the homestay owners in Kuching, Sarawak.